Kongsinyasi Dengan Akad Mudharabah Perspektif Adiwaraman Azwar Karim Dan Muhammad Syafi’i Antonio - Fahrul Ubed; Mugiyati Mugiyati (Pusat Riset dan Inovasi Nasional, 2025)
Consignment or selling is a form of sales that is currently carried out by many MSMEs in Indonesia and carries minimal risk. In Islamic law, the practice of consignment sales is a form of sales using a mudharabah contract. Given this phenomenon, the aim of this article is to understand and analyze consignment sales with mudharabah contracts from the perspective of Adiwarman Azwar Karim and Muhammad Syafi'i Antonio. The data analysis method in this research uses literature reviews from several journals and books related to the thoughts of Adiwarman Azwar Karim and Muhammad Syafi'i Antonio regarding mudhorobah contracts with the principle of profit sharing which is then linked to the practice of consignment sales. The results of this research show that consignment is an application of contemporary economics with mudhorobah agreements and profit sharing in accordance with Islamic law.